The effects of nebivolol and irbesartan on postdialysis and ambulatory blood pressure in patients with intradialytic hypertension: a randomized cross-over study. Issue 2 (February 2019) - Bikos, Athanasios; Loutradis, Charalampos; Angeloudi, Elena; Karpetas, Antonios; Raptis, Vasilios; Kalaitzidis, Rigas; Panagoutsos, Stylianos; Pasadakis, Ploumis; Balaskas, Ilias; Liakopoulos, Vassilios; Papagianni, Aikaterini; Sarafidis, Pantelis A.
Abstract : Objectives: Intradialytic hypertension is estimated at 5–15% of hemodialysis patients and is associated with poor prognosis. Studies on therapeutic interventions for this entity are extremely few. We aimed to evaluate the effects of nebivolol and irbesartan on peridialytic, intradialytic, and ambulatory BP in patients with intradialytic hypertension. Methods: This is a pilot randomized-cross-over study in 38 hemodialysis patients (age: 60.4 ± 11.1 years, men: 65.8%) with intradialytic hypertension (intradialytic SBP rise ≥10 mmHg at ≥4 over six consecutive sessions]. After baseline evaluation, patients were randomly assigned to nebivolol 5 mg and subsequently irbesartan 150 mg, or vice versa. Nineteen patients received a single drug-dose 1 h before hemodialysis and 19 received the drug for a week before evaluation. A 2-week wash-out period took place before the initiation of the second drug. Patients had three respective 24-h ambulatory BP measurements starting before a midweek session. Results: In total, 20 (52.6%) patients received nebivolol first and 18 (47.4%) received irbesartan. Patients receiving a single dose of either drug had lower postdialysis BP (baseline: 160.2 ± 17.8/93.2 ± 13.6 mmHg; nebivolol: 148.0 ± 20.8/84.5 ± 13.1 mmHg, P  = 0.013/ P  = 0.027; irbesartan 142.9 ± 29.9/87.2 ± 18.1 mmHg, P  = 0.003/ P  = 0.104 for SBP and DBP, respectively). The 24-h BP presented a trend towards reduction, but was significant only for 24-h DBP in the nebivolol arm. Patients on weekly administration of either drug had lower postdialysis BP (baseline: 162.5 ± 16.8/95.4 ± 12.7 mmHg; nebivolol: 146.7 ± 16.3/91.8 ± 12.2 mmHg, P  = 0.001/ P  = 0.235; irbesartan: 146.0 ± 23.9/85.8 ± 12.9 mmHg, P  = 0.004/ P  = 0.007, respectively), lower intradialytic BP and lower 24-h BP (baseline: 148.3 ± 12.6/90.2 ± 9.0 mmHg; nebivolol: 139.2 ± 10.6/85.0 ± 7.7 mmHg, P  < 0.001/ P  = 0.001; irbesartan: 142.4 ± 16.4/85.1 ± 9.9 mmHg, P  = 0.156/ P  = 0.030). No significant differences were observed in comparisons between the two drugs, with the exception of heart rate, being lower with nebivolol. Conclusion: Both nebivolol and irbesartan reduced postdialysis and 24-h BP in patients with intradialytic hypertension. Weekly administration had greater effect and nebivolol was numerically slightly more potent than irbesartan.